Markets and MinoritiesMarkets and Minorities by SowellThomas New York: Basic Books, 1981, 141 pp., $13.50 cloth, $5.95 paper. - Becker, Boris W. (Academy of Management Review, 1983)
This article presents a review of the book ?Markets and Minorities,? by Thomas Sowell.